The MASC/BGMP Architecture for Inter-Domain Multicast Routing - Kumar, Satish; Radoslavov, Pavlin; Thaler, Dave; Alaettinoğlu, Cengiz; Estrin, Deborah; Handley, Mark (ACM SIGCOMM'98, 1998)
Multicast routing enables efficient data distribution to multiple recipients. However, existing work has concentrated on extending single-domain techniques to wide-area networks, rather than providing mechanisms to realize inter-domain multicast on a global scale in the Internet. We describe an architecture for inter-domain multicast routing that consists of two complementary protocols. The Multicast Address-Set Claim (MASC) protocol forms the basis for a hierarchical address allocation architecture. It dynamically allocates to domains multicast address ranges from which groups initiated in the domain get their multicast addresses. The Border-Gateway Multicast Protocol (BGMP), run by the border routers of a domain, constructs inter-domain bidirectional shared trees, while allowing any existing multicast routing protocol to be used within individual domains. The resulting shared tree for a group is rooted at the domain whose address range covers the group’s address; this domain is typically the group initiator’s do- main. We demonstrate the feasibility and performance of these complementary protocols through simulation. This architecture, together with existing protocols operating within each domain, is intended as a framework in which to solve the problems facing the current multicast ad- dressing and routing infrastructure.